Psoriasis herpeticum due to Varicella zoster virus: A Kaposi's varicelliform eruption in erythrodermic psoriasis - Geeta Garg; Gurvinder P Thami (Wolters Kluwer Medknow Publications, 2012)
Kaposi's varicelliform eruption (KVE) or eczema herpeticum is characterized by disseminated papulovesicular eruption caused by a number of viruses like Herpes simplex virus I and II, Coxsackie virus, and Vaccinia and Small pox viruses in patients with pre-existing skin disease. The occurrence of KVE with psoriasis has been reported recently as a new entity psoriasis herpeticum. The rare causation of psoriasis herpeticum due to Varicella zoster virus in a patient with underlying psoriasis is being reported for the first time.